2018
DOI: 10.3393/ac.2018.03.13
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors and Bowel Preparation for Screening Colonoscopy

Abstract: PurposeThe quality of bowel preparation is a major determinant of the quality of colonoscopy. This study evaluated lifestyle factors, including usual dietary style, associated with bowel preparation.MethodsThis retrospective study evaluated 1,079 consecutive subjects who underwent complete colonoscopy from December 2012 to April 2014 at National Cancer Center of Korea. Questionnaires on bowel preparation were completed by the subjects, with the quality of bowel preparation categorized as optimal (excellent or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…A number of previous, mostly smaller, studies have assessed the prevalence and risk factors of poor bowel preparation in screening and clinical settings as shown in Supplementary Table S1 [ 8 , 12 , 13 , 14 , 15 ]. The association of inadequate bowel preparation with older age may be explained by a worse mental and functional state.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous, mostly smaller, studies have assessed the prevalence and risk factors of poor bowel preparation in screening and clinical settings as shown in Supplementary Table S1 [ 8 , 12 , 13 , 14 , 15 ]. The association of inadequate bowel preparation with older age may be explained by a worse mental and functional state.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal visualization during colonoscopy is contingent on an adequate bowel preparation, yet only 67.5 % to 78.3 % of patients have an adequate preparation 38 . The finding in our study of increasing GoLytely prescriptions with rising BMI adheres to recommendations borne out of prior studies demonstrating that GoLytely is more efficacious than MiraLAX in the obese population 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in our study, a higher percentage of inadequate bowel preparation scores (BPPS score 0–3) were still observed among obese patients versus the normal BMI subgroup. Several studies have found that an increased BMI is an independent predictor of an inadequate bowel preparation 10 16 38 40 . An inadequate bowel preparation is associated with higher rate of missed lesions, decreased CIR, prolonged procedures, increased patient discomfort, need for repeat procedure, and increased risk for sedation-related adverse events, all of which can contribute to higher healthcare costs 2 22 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is metabolic turbulence associated with various gastrointestinal diseases, including intestinal polyps and colorectal cancer(Liu et al, 2019), affecting bowel preparation quality. Some articles reported that BMI greater than 25 is a risk factor for poor bowel preparation (Hyun et al, 2018). Other studies said BMI greater than 30 is an independent risk factor for inadequate preparation(Fayad et al, 2013).…”
Section: Discussionmentioning
confidence: 99%